EVELYN WAUGH’S STYLE AND ITS IMPACT ON HIS FOLLOWERS’ WORKS. (JULIAN MITCHELL, ANDREW SUNCLAIR, MALCOLM BRADBURY) - Elmira Muratova; Satishova Fariza (Journal of new century innovations, 2023)
Annotation: This article based on the works Evelyn Waugh, Julian Mitchell, Andrew Sunclair, Malcolm Bradbury.